Spatial transcriptomics reveals distinct role of monocytes/macrophages with high FCGR3A expression in kidney transplant rejections - Chen Wongworawat, Yan; Nepal, Chirag; Duhon, Mark; Chen, Wanqiu; Nguyen, Minh-Tri; Godzik, Adam; Qiu, Xinru; Li, Wei Vivian; Yu, Gary; Villicana, Rafael; Zuppan, Craig; De Vera, Michael; et al. (Frontiers in Immunology, 2025)
IntroductionKidney transplant rejections are classified as active antibody mediated rejection (AMR) and cell mediated rejection (TCMR), with AMR primarily driven by antibodies produced by B cells, whereas TCMR is mediated by T lymphocytes that orchestrate cellular immune responses against the graft. Emerging evidence highlights the essential roles of innate immune cells in rejections, especially monocytes/macrophages and natural killer (NK) cells. However, the roles of specific innate immune cell subpopulations in kidney allograft rejection remain incompletely understood.MethodsWe performed the spatial transcriptomics using the formalin-fixed paraffin-embedded (FFPE) core needle biopsies from human kidney allografts.ResultsWe demonstrated that non-rejection, AMR, acute TCMR and chronic active AMR have distinct transcriptomic features. Subclusters of monocytes/macrophages with high Fc gamma receptor IIIA (FCGR3A) expression were identified in C4d-positive active AMR and acute TCMR, and the spatial distribution of these cells corresponded to the characteristic histopathological features. Key markers related to monocyte/macrophage activation and innate alloantigen recognition were upregulated, along with metabolic pathways associated with trained immunity in AMR and TCMR.DiscussionTaking together, these findings revealed that intragraft monocytes/macrophages with high FCGR3A expression play a critical role in kidney transplant rejections.